PEMANFAATAN FASILITAS BELAJAR PADA MATA PELAJARAN AL-QUR’AN HADITS DI SEKOLAH DASAR NEGERI 1 JONGKONG - Nasution, Nasution (JIP: Jurnal Ilmu Pendidikan, 2025)
The objectives of this study are (1) to identify the learning facilities used to support the process of learning the Qur'an and Hadith at Jongkong 1 Public Primary School. (2) To determine how teachers utilise learning facilities to support the process of learning the Qur'an and Hadith at Jongkong 1 Public Elementary School. (3) To identify obstacles in utilising learning facilities to support the process of learning the Qur'an and Hadith at Jongkong 1 Public Elementary School. This study used a qualitative approach with a descriptive method. The facilities have been utilised well and appropriately in supporting the Al-Qur'an Hadith learning process, but there are still several obstacles faced by Al-Qur'an Hadith teachers in using learning facilities. These obstacles can be overcome with other facilities and the creativity of Al-Qur'an Hadith subject teachers. Other obstacles experienced by teachers in utilising learning facilities at school are more related to the situation and conditions, especially for learning rooms and libraries. Facilities that can support Al-Qur'an Hadith learning include the school library and prayer room.